Designer drugs : chemistry, analysis, regulation, toxicology, epidemiology & legislation of new psychoactive substances - Gerona, Roy (Elsevier, 2024)
A title in the Emerging Issues in Analytical Chemistry series, Designer Drugs: Chemistry, Analysis, Regulation, Toxicology, Epidemiology & Legislation of New Psychoactive Substances presents both an overview and a guide to techniques for designer drug analysis. Proliferation of the synthesis and use of designer drugs is a serious public health problem with social, economic, and legal implications. Whether abuse is studied at the population level or the individual level, researchers need both background and highly detailed technical information on specific drugs and drug classes in order to combat the proliferation and highly damaging consequences of these substances. Author Roy Gerona provides a comprehensive discussion that emphasizes the potential threat to society, presents the ongoing challenges confronting the various laboratory approaches to detection and identification of new chemical entities, and informs the development of improved analytical solutions for use in legislation, law enforcement, and treatment. Designer Drugs: Chemistry, Analysis, Regulation, Toxicology, Epidemiology & Legislation of New Psychoactive Substances offers an introduction to the field and a source of information on specific drugs, drug effects, and analytical tools to a wide audience for anyone studying or engaging in designer drug analysis. Analytical and medical chemists, pharmacologist, toxicologists, and students, researchers, and policy makers in the fields of drug abuse, medicine, public health, and forensics will greatly benefit from this essential text.Summarizes available literature and evaluates the strengths and weaknesses of analytical methods for detecting and identifying designer drugsDirects the reader to sources of further reading at the conclusion of each chapterEmphasizes the potential threat to societyPresents ongoing challenges confronting various laboratory approaches to detection and identification of new chemical entities